Boganmeldelser - Paul Larsson; Annette Esdorf; Patrick Gosden; Beth Grothe Nielsen; Ida Koch; Catharina Juul Kristensen; Heidi Mork Lomell; Hans Henrik Brydensholt; Claes Levin; Terttu Utriainen; Minna Kimpimäki; Helgi Gunnlaugsson; et al. (Nordisk Tidsskrift for Kriminalvidenskab)
Intet resumé